2019
DOI: 10.1002/epi4.12373
|View full text |Cite
|
Sign up to set email alerts
|

Subtraction Ictal SPECT coregistered to MRI (SISCOM) as a guide in localizing childhood epilepsy

Abstract: Objective To assess feasibility and efficacy of subtraction ictal SPECT coregistered to MRI (SISCOM) for epilepsy localization in children who are candidates for resective surgery. Methods We retrospectively reviewed all patients ≤16 years with drug‐resistant epilepsy screened for epilepsy surgery in the University Hospital of Leuven from January 2009 to January 2018. Fifty‐eight hospitalizations for ictal SPECT and 51 SISCOM analyses in 44 patients were included. Mean age was 9.1 years. Hospitalizations for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
(97 reference statements)
1
2
0
Order By: Relevance
“…Our results are in agreement with previous findings, although studies have previously reported better results with respect to odds ratio of good outcome [17]. On the other hand, very few studies have evaluated the concordance of SPECT localization with surgical outcomes [28][29][30]. A previously conducted meta-analysis predicted better outcome for SPECT findings than was reported in our study [31].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with previous findings, although studies have previously reported better results with respect to odds ratio of good outcome [17]. On the other hand, very few studies have evaluated the concordance of SPECT localization with surgical outcomes [28][29][30]. A previously conducted meta-analysis predicted better outcome for SPECT findings than was reported in our study [31].…”
Section: Discussionsupporting
confidence: 93%
“…Automated injectors can reduce lag time from 60 s with hand administration to 18.5 s using an automated method ( 175 ). Since seizure activity is initially limited to the focus/foci, but then spreads to adjacent or even contralateral brain areas, capturing the perfusion pattern early increases the accuracy of the localization by perfusion SPECT ( 176 , 177 ). For example, using automated injectors increased localization of seizure foci from 62.9 to 81.8% ( 175 ).…”
Section: Assessment Of the State Of The Art—spect In Brain Disordersmentioning
confidence: 99%
“…Ictal single-photon emission computed tomography (SPECT) may identify areas of hyperperfusion while subtraction of ictal-interictal SPECT co-registered to MRI (SISCOM) has been shown to provide high sensitivity and specificity for identification of an EZ, particularly in temporal lobe locations in both adult and pediatric patients. 26 , 27) This technique is limited by the resource-intensiveness implicit to obtaining ictal studies. MEG or functional MRI (fMRI) may have utility in surgical planning by way of providing identification of eloquent cortex.…”
Section: Natural Historymentioning
confidence: 99%